Controlling Antimicrobial Activity of Quinolones Using Visible/NIR Light-Activated BODIPY Photocages - Elena Contreras-García; Carmen Lozano; Cristina García-Iriepa; Marco Marazzi; Arthur H. Winter; Carmen Torres; Diego Sampedro (MDPI AG, 2022)
Controlling the activity of a pharmaceutical agent using light offers improved selectivity, reduction of adverse effects, and decreased environmental build-up. These benefits are especially attractive for antibiotics. Herein, we report a series of photoreleasable quinolones, which can be activated using visible/NIR light (520-800 nm). We have used BODIPY photocages with strong absorption in the visible to protect two different quinolone-based compounds and deactivate their antimicrobial properties. This activity could be recovered upon green or red light irradiation. A comprehensive computational study provides new insight into the reaction mechanism, revealing the relevance of considering explicit solvent molecules. The triplet excited state is populated and the photodissociation is assisted by the solvent. The light-controlled activity of these compounds has been assessed on a quinolone-susceptible E. coli strain. Up to a 32-fold change in the antimicrobial activity was measured.